2019
DOI: 10.1021/acsami.9b12946
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Electrode Kinetics for Discrimination of Dopamine by a PEDOT:COOH Interface Doped with Negatively Charged Tricarboxylate

Abstract: Figure S1. Cyclic voltammetry (CVs ) and Chronoamperometry (CA) electropolymerization of PEDOT by 10 mM EDOT with 20 mM citrate (a1-2), 20 mM LiClO4 (b1-2), 10 mM citrate and 20 mM LiClO4 (c1-2) as dopant and supporting electrolyte; inset of a2, b2 c2 are the corresponding charge of CA electropolymerization. CVs of CA-electropolymerised PEDOT:C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…The existence of bands at 1750 and 1680 cm -1 related to -C=O for PEDOT-COOH25%100%, implies the successful co-polymerisation of EDOT-COOH into the Nano-PEDOT-COOH matrix. The total surface density of carboxylic acid groups on the Nano-PEDOT-COOH surfaces was quantified by the TBO staining technique as previously reported (Meng et al 2019a;Rödiger et al 2011). Figure 1d displays the linear increase of carboxylic acid group density from 0.03 µmol cm -2 for PEDOT-COOH25% to 0.18 µmol cm -2 for PEDOT-COOH100%.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The existence of bands at 1750 and 1680 cm -1 related to -C=O for PEDOT-COOH25%100%, implies the successful co-polymerisation of EDOT-COOH into the Nano-PEDOT-COOH matrix. The total surface density of carboxylic acid groups on the Nano-PEDOT-COOH surfaces was quantified by the TBO staining technique as previously reported (Meng et al 2019a;Rödiger et al 2011). Figure 1d displays the linear increase of carboxylic acid group density from 0.03 µmol cm -2 for PEDOT-COOH25% to 0.18 µmol cm -2 for PEDOT-COOH100%.…”
Section: Resultsmentioning
confidence: 80%
“…Fourier transform infrared (FTIR) spectroscopy was performed using a VERTEX spectrometer (Bruker, USA) equipped with an attenuated total reflection (ATR) measuring cell. The density of carboxylic acid groups on different Nano-PEDOT-COOH biointerfaces were examined via toluidine blue O (TBO) staining assay (Meng et al 2019a). In brief, PEDOT-COOH electrodes (0.6 cm 2 ) were incubated in 2 mM TBO solution (0.1 mM KOH) for 2 h. Under alkaline conditions, the carboxylic acid groups deprotonate to bind with the positively charged TBO molecules with a ratio of 1:1.…”
Section: Characterisations and Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution SEM confirmed that MOF525 was attached to the surface of PEpC ( Figure 8 b). The CV diagrams showed that the PEpC modified microelectrode was also catalytically active for DA ( Figure 8 c), where the catalytic capability may be ascribed to the carboxylic group [ 51 ]. The MOF525/PEpC modified microelectrode exhibited a more distinct oxidation peak, and the S/B ratio reached 1.74.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the initial spike of current corresponding to the charging of the double layer at S-RGO was 243 mA, which is much larger than those of GO (73 mA) and RGO (39 mA). Moreover, the interfacial capacitance 41 of the resulted PEDOT:S-RGO ( Fig. S5, ESI †) was estimated to be 14.4 mF cm À2 , which is 2.8 and 7.8 times higher than that of PEDOT:RGO (5.1 mF cm À2 ) and PEDOT:GO (1.8 mF cm À2 ), respectively.…”
Section: Efficient Electropolymerisation Of Pedot Doped With S-rgo (Pmentioning
confidence: 98%